Tratamiento contable de las cuentas por pagar y cobrar de la Compañía de transporte de carga pesada Comtrariovin S.A. - Palma Arcentales, Ana María (2017)
The Heavy Freight Transport Company COMTRARIOVIN SA, carries out its operations as a transport service provision, in the province of Los Ríos of the Vinces canton, the person in charge of safeguarding the interests of the company is Mr. Luis Piedrahita Bohórquez as General Manager , the same that with strategies and vigor controls the financial procedures of the entity COMTRARIOVIN, the company is founded with the objective of obtaining authorization to operate in the main activity to generate profitability, these heavy goods vehicles are owned by the shareholders that make up the group for profit, at the end of the accounting cycle it is expected that the profit will be distributed in dividends and be able to achieve the proposed results as a cargo transport entity and to strengthen public and private relations to reach the demand with our service . It is important to study professionalism in the way the entity carries out its procedures in the application and accounting control, which in the development of the case study we can account for the shortcomings that arise in the movements of the income account, accounts receivable and accounts payable, since they are one of the items with greater relevance to the operation of the group, these items generate movements that are recorded in the accounting process for the receipt of money for the negotiation of the cargo service , this contract is not carried with the commercial documents of the entity, but through the invoices issued by each partner in the activity of carrier, as a taxpayer, preventing the accounting record is expressed in the books of the company and in the heading of the box item - banks of the same one, it is so the society is being affected in its economic results taking it to a complex environment with the internal and / or external consumer, before their control organisms.